Modeling of photons trapping effect on the performance of HPT-LED Optoelectronic Integrated Device (OEID) - Eladl, Sh.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The effect of photons trapped at the LED side due to total internal reflection on the transient behavior of an Optoelectronic Integrated Device (OEID) is considered in this paper. The device is composed of a Heterojunction Phototransistor (HPT) and a Light Emitting Diode (LED). The expressions describing the transient response of the output photons flux, the rise time, and the output derivative are derived. The effect of the various device parameters on the transient response is outlined. The results show that the transient response of these types of devices is strongly dependent on the ratio of these trapped photons in the LED part. Also the device under consideration can be changed from switching mode to the amplification mode, if the fractions of trapped photons exceed a specified value. This type of the model can be exploited as an optical amplifier, optical switching device and other applications.